Human age estimation based on facial images - Zhao, Wei (2017)
With the rapid development of computer vision, pattern recognition and biometrics, more and more attention has been paid to computer-based human facial age estimation, which is widely used when an individual's age needs to be obtained without specifically identifying other irrelevant personal information. Thus it has broad computer vision applications including security surveillance, forensics, biometrics, human-computer interaction (HCI), electronic customer information management, age-specific precision marketing (like age-based visual advertisement), entertainment and so on. There are quantities of realistic scenarios where facial age estimation can be put to good use: with a monitoring camera the juveniles can be warned or even stopped from purchasing cigarettes or banned drugs from vending machines; the underage can be prevented from entering wine bars and buying alcohol drinks; the elders can be cautioned when they want to try some high-risk rides in theme parks, like roller coasters and forest adventures; children's entry into harmful websites can also be restrained which contain violence, pornography or other restricted contents, etc.